Money demand models for Russia: A sectoral approach - Anna Krupkina; Alexey Ponomarenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
We estimate money demand models for certain monetary aggregates across different institutional sectors (a novelty for the Russian case). Our results comprise a collection of money demand equations that include different combinations of explanatory variables. Comparing the validity of these models on the basis of statistical criteria is virtually implausible. Therefore we suggest the simultaneous employment of a whole set of such models and illustrate the approach by presenting the distribution of monetary overhangs calculated on the basis of the estimated models.
URN:NBN:fi:bof-201408072131
Keywords: E41; C22; D14; D22; 330; monetary aggregates; money demand; households; non-financial corporations